Innovations in Microteaching: Web-Based Approaches to Pedagogical Skill Development - Azi Nurazima Juhastri; Welven Aida; Pipit Rahayu; Eripuddin Eripuddin (AL-ISHLAH: Jurnal Pendidikan, 2026)
The shift to digital learning environments, accelerated by the COVID-19 pandemic, has prompted innovations in teacher education, including the use of web-based microteaching. While traditional microteaching enhances instructional skills, it often lacks flexibility and digital engagement. This study investigates how web-based microteaching supports pedagogical skill development in pre-service English teachers. This qualitative case study involved 25 undergraduate students enrolled in a Microteaching course at the University of Pasir Pengaraian. Data were collected through recorded teaching videos, reflective journals, structured observation checklists, and semi-structured interviews. Participants completed three teaching cycles—two synchronous and one asynchronous—over a 16-week semester. Data were analyzed thematically using Braun and Clarke’s (2006) method and organized using NVivo 12 software. Findings showed significant improvement in lesson planning, instructional clarity, classroom management, and reflective depth. Teaching videos demonstrated enhanced lesson structure, use of questioning strategies, and purposeful digital tool integration. Reflective journals evolved from general self-evaluations to more analytical reflections. Peer and instructor feedback, facilitated through digital platforms, played a critical role in supporting iterative development. Web-based microteaching proved effective in fostering both pedagogical competence and digital fluency. Participants reported increased teaching confidence and began to view themselves as emerging professionals. Despite initial technical challenges, repeated practice supported the development of adaptive teaching strategies. These results suggest that structured online microteaching can be a sustainable model for contemporary teacher education.